BEBAN KERJA MENTAL DENGAN METODE NASA TLX PADA KARYAWAN TERMINAL LPG TANJUNG SEKONG - J, Neti Wanti; Maulani, Syifa Fajar; Masuroh, Jakiyah; Huwaiza, Rayyan Dzikru (Inaque : Journal of Industrial and Quality Engineering, 2024)
Valuable assets for companies are not only things related to objects or securities. However, company assets that are no less important than these things are qualified human resources. Employees with good performance contribute positively to the company. Therefore, optimal management is required. This research was conducted at Tanjung Sekon LPG Terminal, which is one of the terminals located in Cilegon City, Banten. The population size is 106 employees, and a sample of 52 employees was taken using the Slovin method. Mental workload was measured using the NASA-TLX method. Based on the results obtained, it can be determined that 5 employees have a moderate mental workload, 34 employees have a high mental workload score, and 13 employees have a very high mental workload. Based on the comparison of NASA TLX elements, the most dominant result among the 52 employees is that 31.5% of employees have high mental demand (MD), followed by 23.6% of employees with high temporal demand (TD), and 22.8% of employees with high physical demand (PD).